Research of phishing detection technology - Xi ZHANG; Zhi-wei YAN; Hong-tao LI; Guang-gang GENG (网络与信息安全学报)
The current status of phishing scams were analyzed and the data sets and evaluation indicators commonly used in phishing detection were summaried.On this basis,a detailed overview of the typical methods of phishing detection was given,which included blacklist strategies,heuristic methods,visual matching methods,and methods based on machine learning and natural language processing.The comparison and analysis of those methods were given,and furtherly,the challenges and future trends of phishing detection were discussed.